Teun A. van Dijk's Critical Discourse Analysis of the Indonesian House Speaker's 2024 Annual and Joint-Session Speech (Oratio Directa, 2025)
This study examines the speech delivered by the Speaker of the Indonesian House of Representatives, Puan Maharani, at the MPR Annual Session and the joint DPR–DPD session on 16 August 2024. It applies Teun A. van Dijk's critical discourse analysis framework to three interconnected dimensions: text, social cognition, and social context. Textual analysis covers macrostructure, superstructure, semantics, lexicon, syntax, style, and rhetoric. The speech foregrounds national unity, electoral ethics, democratic checks and balances, women's participation, human-resource development, and public oversight. Positive lexical choices, inclusive formulations, contrast, repetition, and institutional metaphors construct the DPR as a democratic and people-oriented institution while criticizing coercive or unfair electoral practices. The analysis relates these textual strategies to the post-election transition and the institutional position of the DPR. However, the source does not report interviews, production documents, or direct evidence of the speaker's mental models. Claims concerning a pro-status-quo ideology or communicative intent must therefore be treated as discourse-based inferences rather than established cognitive facts. The study demonstrates the value of integrating textual and contextual analysis while requiring stronger evidence for claims about cognition and audience effects.
Keywords: Critical discourse analysis; Social cognition; Social context; Political speech; Teun A. van Dijk